Komunikasi Pascapembelian untuk Menjaga Kepercayaan Konsumen (Keterlibatan Konsumen Tinggi dalam Pembelian Produk Smartphone) - Erna M Susilowardhani (Jurnal InterAct, 2012)
Sales orientation is not the only indication of a successful product. Another important factor is the orientation to the consumer. Moreover, consumers are increasingly aware of their need and also more critical with the products they need. Therefore, manufacturers need to ﬁnd ways to be able to offer products that meet the expectations of the consumers so that consumers feel satisﬁ ed. Maintaining consumer conﬁdence in the product being offered is absolutely done by the manufacturer. Even more, there is a need to understand the purchase decision-making process of the consumers, especially for high price products. In this article, the author focuses on the study of smartphone products. The author does not focus on a single brand, but in general of smartphone products.  This article describes how important a post-purchase communication and how long will it take to conduct a post-purchase communication in maintaining consumer conﬁdence. Consumers will believe in the productivity they are satisﬁed. Not just related to the value of the product, but also satisﬁed with the services to consumers. Not only the services at the time of purchase but also post-purchase. Of course, with conﬁdence and satisfaction achieved by the consumers, will make consumers become loyal with the product.